PREPARATION AND OPTIMIZATION OF GEPIRONE HCL SR MATRIX TABLETS USING HPMC K100M AND POLYOX WSR N80 - DAS, DINESH; KUMAR, ANJAN; PATRA, CH. NIRANJAN (International Journal of Applied Pharmaceutics, 2025)
Objective: In adults, Gepirone Hydrochloride (HCl) is most commonly employed as a first-line treatment for Major Depressive Disorder (MDD). The elimination half-life of Gepirone HCl is approximately 5 h necessitates the development of sustained release formulation. In the current research, two polymers HPMC K100M and Polyox WSR N80 were used in combination by adopting a central composite design with an objective to minimize burst release and sustain drug release for 24 h. Methods: The SR matrix tablets of Gepirone HCl were prepared by wet granulation method. Optimization of Gepirone HCl SR matrix tablets was achieved through central composite design (CCD). The selected CQAs were concentration of polymer HPMC K100M in the range of 20 to 40 mg per tablet and concentration of Polyox WSR N80 in the range of 30 to 50 mg per tablet. Three responses selected for optimization vis-à-vis Q 1 (Cumulative percent drug release from SR matrix tablet in 1 h), t 50 (time taken for release of 50% of API) and Q 18 (Cumulative percent drug release from SR matrix tablet at 18 h). Results: Fourier Transform Infra Red (FT-IR) and Differential Scanning Calorimetry (DSC) study for the physical mixture of Gepirone HCl with HPMC K100M and Polyox WSR N80 in 1:1 ratio demonstrated compatibility. The granules exhibited improved flowability and compressibility. The optimized formulation (run 7) passed all the quality control tests for tablets. Scanning electron microscopy for tablet of run 7 exhibited a homogenous and porous gel network. In vitro dissolution study showed that the integration of two polymers HPMC K100M and Polyox WSR N80 were effective in minimizing the initial burst release, and sustained release of Gepirone HCl over 24 h. Conclusion: Hence, the development of a once-daily formulation aligns with modern patient-centric approaches in pharmaceutical design, catering to convenience and improving quality of life for patients requiring long-term therapy.